Effects of precipitation and temperature on the growth variation of Scots pine — A case study at two extreme sites in Finland - Nöjd, Pekka; Korpela, Mikko; Hari, Pertti; Rannik, Üllar; Sulkava, Mika; Hollmén, Jaakko; Mäkinen, Harri (Elsevier, 2017)
Site properties have received limited attention in analyzing the weather-growth relationship of trees. We analyzed the annual growth variation of Scots pine on two extreme sites in southern Finland: a dry hill top site and a moist patch of mineral soil surrounded by a large peatland. The effects of daily precipitation and temperature were related to growth variation using correlation analyses. In addition, the common signal and the difference of ring-width indices from the dry and moist sites were studied via principal component analysis and related to the daily weather measurements. All possible time intervals longer than 14 days from current year April 1st to August 31st were tested. We also modeled daily photosynthetic production of Scots pine using two parameter sets, one describing limited stomatal closure and the other one easily triggered stomatal closure. Growth variation at the dry site was linked with variation of precipitation during early and middle parts of growing season, while growth at moist site was correlated with temperature during the middle part of growing season. Daily photosynthetic production, modeled with parameters describing mostly open stomata produced a rather strong negative correlation with ring-width indices from the dry site, possibly indicating that the parametrization overestimated growth during dry years. Other than that, the modeled photosynthetic production was relatively weakly correlated with the ring-width indices. Evidently, the mechanisms controlling Scots pine growth at drought-sensitive sites in southern Finland are complex. Overall, the results indicate that site properties, especially water retention capacity, need to be considered in dendroecological research.
Keywords: tree ring; site properties; photosynthetically active radiation; growth rings; photosynthesis; properties; drought; radiation